2006
DOI: 10.2165/00002018-200629100-00139
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the Diabetes, Metabolic Syndrome and Metabolic Abnormalities in Schizophrenia over the Course of the Illness: a Cross-Sectional Study

Abstract: Background: Patients with schizophrenia are at high risk of developing metabolic abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
78
2
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 35 publications
(38 reference statements)
9
78
2
3
Order By: Relevance
“…The recent literature is relatively consistent in showing a prevalence rate of diabetes of about 15% in patients with schizophrenia or an increased risk of two to threefold as compared to the general population [17]. Such a high prevalence of diabetes and metabolic syndrome in schizophrenia over the course of the illness has been confirmed in a cross-sectional study performed by our group [25]. It is noteworthy that this higher prevalence of diabetes or abnormal glucose metabolism is also found in drug-naïve patients.…”
Section: Psychiatric Disorders and Diabetessupporting
confidence: 67%
See 1 more Smart Citation
“…The recent literature is relatively consistent in showing a prevalence rate of diabetes of about 15% in patients with schizophrenia or an increased risk of two to threefold as compared to the general population [17]. Such a high prevalence of diabetes and metabolic syndrome in schizophrenia over the course of the illness has been confirmed in a cross-sectional study performed by our group [25]. It is noteworthy that this higher prevalence of diabetes or abnormal glucose metabolism is also found in drug-naïve patients.…”
Section: Psychiatric Disorders and Diabetessupporting
confidence: 67%
“…Nevertheless, the lack of a significant increase in mean blood glucose in comparator groups would suggest a causal relationship between atypical antipsychotics and diabetes. [10,11,25] Several pharmacoepidemiological studies examining the association between antipsychotic drugs and diabetes have produced confusing results [38][39][40][41]. The studies rely on the analysis of computerized databases of patients treated in various organizations and are limited by the quality of clinical data recorded.…”
Section: Antipsychotics and Glucose Disturbancesmentioning
confidence: 99%
“…In consistent with previous studies, waist circumference was larger in women (17,32). De Hert and associates (50) reported that the most common MetS criteria among first episode, (<1.5 years), new onset (1.5-10 years), subchronic (10-20 years) and chronic (>20 years) schizophrenia patients was waist circumference. These findings suggest that waist circumference is an important criteria to follow the patients.…”
Section: One Of the Most Important Causes For Mets In Patientsmentioning
confidence: 99%
“…Overweight and particularly obesity predicts cardiovascular risk, metabolic syndrome (MS) and diabetes mellitus type 2 (DM-II) [1][2][3][4][5] as well as an increased risk for cancer [6,7].…”
Section: Introductionmentioning
confidence: 99%